Use of Axathioprine for Nongranulomatous Ulcerative Jejunoileitis. (1st September 1997) - Enns, Robert; Lay, Thomas; Bridges, Ronald
Abstract : Nongranulomatous ulcerative jejunoileitis (NGUJI) is a rare, often fatal disorder that produces multiple nonmalignant small bowel ulcerations. A 55-year-old woman with presumed celiac disease presented with steroid-refractory diarrhea, weight loss and abdominal pain. A laparotomy was performed to exclude the possibility of a lymphomatous disorder, and multiple nonmalignant small bowel ulcerations were discovered. Despite a combination of treatment with total parenteral nutrition (TPN) and prednisone 30 mg/day she continued to deteriorate. The addition of azathioprine to her treatment regimen resulted in marked clinical and biochemical improvement. Her enteroscopy normalized, and she was able to discontinue TPN and reduce her steroid requirements. Although azathioprine has been used occasionally to treat refractory sprue, there have been no reports of its use in NGUJI. In this case, azathioprine played a key role in the management of NGUJI and should be considered a treatment option for patients with this disorder.